Wettbewerbsveränderungen im Kontext der Smart-Meter-Einführung in Deutschland - Torsten J. Gerpott (Wirtschaftsdienst, 2017)
In Deutschland werden in den nächsten Jahren die Stromzähler von Millionen von Stromletztverbrauchern und Betreibern dezentraler Energieerzeugungsanlagen durch vernetzte intelligente Messsysteme, die auch als Smart Meter bekannt sind, ersetzt. Vor dem Hintergrund des gesetzlichen Rahmens und der neuen Fähigkeiten von intelligenten Messsystemen werden Wettbewerbseffekte auf Messsystembetreiber und ihre Zulieferer untersucht. Dabei zeigt sich, dass die verstärkte dezentrale Energieerzeugung aus erneuerbaren Quellen und die damit notwendige Digitalisierung von Elektrizitätsnetzen paradoxerweise zur Verringerung der Zahl überlebensfähiger Messstellenbetreiber beiträgt. – – Triggered by the 'Messstellenbetriebsgesetz' (metering point operations act), millions of electricity end-users and operators of decentralised energy production facilities face the re placement of their electricity meters by networked intelligent measurement systems (iMS; also better known as smart meters) in Germany in the coming years. Against the background of the legal context of iMS and an overview of their new capabilities, the present article discusses competitive effects of their launch on (1) companies that supply key iMS components to the electricity sector and (2) iMS operators. The analysis reveals that the increasing deployment of decentralised plants generating power from renewable sources, in conjunction with the digitalisation of electricity networks, paradoxically promote a decrease in the number of viable metering point operators. This leads to an increase in market concentration among iMS operation suppliers in favour of large scale utilities and financially strong players from outside the electricity industry which sell billing services covering various ancillary consumption costs of rental flats.
Keywords: K23; K32; L10; L86; L94; L96; 330